Role of serum Vitamin-C and lipid profile in cardiovascular diseases patients of Southern Rajasthan - Dhanak, Parul; Sharma, Ashish; Sharma, Neha (International Journal of Research in Medical Sciences, 2019)
Background: Vitamin C's functions as an antioxidant and as an enzyme cofactor are well established, but the ways in which these functions may modify chronic disease risk are less well established. The belief that vitamin C may benefit heart health has stemmed from multiple pieces of evidence and lines of reasoning. Thus, we took the objective of this study to evaluate the correlations of serum concentrations of trace elements including vitamin-C with lipid profile parameters of adult men in Southern Rajasthan. Methods: Present study was conducted in Cardiology and Biochemistry Department in GMCH, Udaipur during the year 2019. A total of 150 MI cases/controls were selected. Blood sample was collected by vein puncture using an aseptic technique. The blood was allowed to settle at 37ºC and then centrifuged at 3000 rpm for 15 min. Serum was then separated and stored at -20ºC until analysis. Vitamin C by NATELSON method on colorimeter. Results: The study cases had significantly higher lipid values than those of controls (p<0.001). In cases the vitamin-C levels were significantly low than the controls. There was significant difference in lipid levels among smokers and nonsmokers. When vitamin C levels were compared there was no statistically significant difference in their levels. There was no significant correlation between serum vitamin C levels and Lipids. Conclusions: The physical characteristics such as diet, residence, smokers, non-smokers, showed significant difference in the controls and cases. Women seemed to have higher proportion of lipid abnormality than men. It is concluded from this study that lower levels of ascorbic acid definitely increase the risk of cardiovascular disease and inclusion of ascorbic acid in the normal diet will control the level of lipids.